Behaviour patterns of the cage-housed breeding flock of pheasants (Phasianus colchicus) - David Zapletal (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
The aim of this work was to investigate the behaviour patterns of a cage-housed breeding flock of pheasants during the day in the early stage of laying period, and evaluate the differences in behaviour patterns between male and female pheasants. Observations were carried out with a flock of common pheasants (Phasianus colchicus) consisting of 1 male and 5 female pheasants aged 2 years that showed a minimum rate of aggression in the previous laying. Behaviour patterns of birds were studied using a 15-minute video recording taken at each hour during the day (from 7 a.m. until 7 p.m.). The rates of activities such as feeding, movement, resting, scratching, preening, mating and aggression in female pheasants differed significantly from those in the male, as observed throughout the day. The rate of feeding had 2 peaks in hens (in early morning and late evening). Generally, the feed intake in females was observed throughout the day whereas the male received feed less frequently but at a higher rate, particularly in the afternoon. The highest rate of movement was observed for both male and female pheasants in morning hours followed by a decline in movement activities which was slow in hens and rapid in the cock, with the subsequent second peak before dark. Except for 7 a.m., resting was among behaviour patterns with the highest rate in both genders throughout day, with lower rates in females as compared to the male. The stereotype behaviour was observed in hens more frequently, with a peak in a period from 9 a.m. to 12 a.m. The highest frequency of mating was observed in the evening after 7 p.m.